Collagen Biomaterials - Mazumder, Nirmal; Chakrabarty, Sanjiban (IntechOpen, 2022)
Collagen is the most abundant protein class in the human body. The polymer also has the distinct benefit of being biodegradable, biocompatible, readily accessible, and very adaptable. The use of collagen-based biomaterials in tissue engineering applications has increased dramatically over the past few years, owing to extensive research in the field. Multiple cross-linking strategies for collagen have been examined. Various combinations of collagen with other biopolymers have also been investigated in an attempt to increase the tissue function of the collagen biomaterials in their various formulations. Collagen Biomaterials provides a thorough overview of the different uses of collagen-based biomaterials produced for tissue engineering, to offer a functional material for use in regenerative medicine from the laboratory bench to the patient bedside.